RESPONS KUMBANG AMBROSIA TERHADAP PERLAKUAN DENG AN PESTISIDA - Paimin Sukartana; Abdurahim Martawijaya; Dominicus Martono (Jurnal Penelitian Hasil Hutan, 1989)
A  case study   on  the  behavioral  responses  of  ambrosia  beetles  to some  pesticidal  formulations   was carried out  at  a logging area in West Kalimantan  in 1981.    Each  pesticide  formulation   was sprayed  to debarked  logs of fresh1%  felled  ramin trees  (Gonystylus bancanus Kurz.}.   The  tested   logs  were,  then,  allowed  for  the  beetle  infestations for  four  weeks,   and inspections  were conducted   weekly  to count  the beetle  tunnels. A  lower  intensity   of  the  beetle   infestation   on  the  treated  logs  than  those  on  the  controls   was  considered  as an inhibitory   response.  in contrast,   a  higher  intensity   of  the  infestation   on  the  treated  logs  was  indicatively   caused  by  a stimulatory    response. These following  conclusions  are drawn  from  this  study:                            1. A  highly  inhibitory   response  on  the  ambrosia  beetle  attacks  was shown  by  treatments   with  pesticide   containing  50% cypermethrin   or  50%  fenithrotion.2. Ramin   logs  treated  with  pesticide   containing   either  30%   TCMTB  or  a  mixture   of  90%  thiourea  + 10%  quarternary ammonium  +  0.1 % diazenium   dioxy   seemed   to  be  highly  stimulating   to  the  beetles.   The  stimulating   effect   of  the second  formulation   initially  decreased  and  lost afterwards  if  the diazenium   dioxy   component  was increased by 0.1   to 0.2%.   A  doubtful    record  was shown   if  the  TCMTB  was mixed   with  2%   borax.3. The pesticide  containing  5%  Cu-8-oxyquinolinolate   and 80% dichlofluanid   were also unaffected to the beetle  responses